2018
DOI: 10.1186/s13293-018-0166-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gut-derived endotoxin on anxiety-like and repetitive behaviors in male and female mice

Abstract: BackgroundGut dysbiosis is observed in several neuropsychiatric disorders exhibiting increases in anxiety behavior, and recent work suggests links between gut inflammation and such disorders. One source of this inflammation may be lipopolysaccharide (LPS), a toxic component of gram-negative bacteria. Here, we (1) determine whether oral gavage of LPS, as a model of gut-derived endotoxemia, affects anxiety-like and/or repetitive behaviors; (2) test whether these changes depend on TLR4 signaling; and (3) test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…Central injection of NPY can result in excessive feeding and reduced energy expenditure in rats [19,20] . In addition, a large number of studies have shown that NPY mainly participates in the regulation of energy balance through NPY1 receptor, NPY2 receptor, and NPY5 receptor [21][22][23][24] . Therefore, in this study we observed the expression levels of NPY5 receptor in ARC in normal rats and obese rats.…”
Section: Discussionmentioning
confidence: 99%
“…Central injection of NPY can result in excessive feeding and reduced energy expenditure in rats [19,20] . In addition, a large number of studies have shown that NPY mainly participates in the regulation of energy balance through NPY1 receptor, NPY2 receptor, and NPY5 receptor [21][22][23][24] . Therefore, in this study we observed the expression levels of NPY5 receptor in ARC in normal rats and obese rats.…”
Section: Discussionmentioning
confidence: 99%
“…This is equivalent to 0.067-91.67 µg/kg endotoxin per day (calculated according to an infant weight of 6 kg and 100 g of milk powder per day, for example). The endotoxin level in milk and milk products is still far from the dose that can cause a severe immune reaction (250 µg/kg) [38][39][40], which suggests that the endotoxin content in milk powder cannot cause disease in infants and young children. However, heat tolerance leads to endotoxin remaining in dairy products.…”
Section: Endotoxin In Infant Foodmentioning
confidence: 99%
“…The oral intake of endotoxin can increase the content of endotoxin in the blood, which leads to an immune response (Table 2). It was found that the concentration of endotoxin in the serum of mice increased by 1.5 times after treatment with 300 µg/kg endotoxin by oral gavage for 2 hours, which also caused the mice to exhibit anxious behavior [40]. The intestine, liver, and lung cytokine-induced neutrophil chemoattractant 1(CINC-1) concentrations in mice fed 250-500 µg of endotoxin orally increased by about four times (equivalent to human IL-8); plasma and lung TNF-α concentrations also increased significantly.…”
Section: Effects On Infant Healthmentioning
confidence: 99%
“…The Gram-negative bacterial membrane component LPS is an endotoxin commonly utilized to study the effects of inflammation on behavior in rodent models, including voluntary ethanol intake, anxiety-like behaviors, and blood-brain barrier integrity [46][47][48][49] . Studies have demonstrated the direct effects of LPS on microglial activation and subsequent neurological pathologies and behaviors.…”
Section: Microbiota-derived Lps and Neural-immune Interactionsmentioning
confidence: 99%